The hot brain : survival, temperature, and the human body - Gisolfi, Carl V.; Mora, Francisco (Mora Teruel) (Bradford book., 2000)
"The book first traces the story of the brain throughout evolution and shows how the control of body temperature as a survival mechanism was achieved. It then goes on to discuss the mechanisms of our environmental independence, why a body temperature of 37[degrees]C (only five degrees from death) is essential for humans, and how this narrow temperature range is defended. It describes how we cope with environmental extremes, the function of fevers, and why thermoregulation is best understood through a combination of physiological and cognitive approaches."--Jacket